Can more information facilitate communication? - Junichiro Ishida; Takashi Shimizu (Osaka University, Institute of Social and Economic Research (ISER), 2012)
In this paper we analyze a cheap talk model with a partially informed receiver. In clear contrast to the previous literature, we find that there is a case where the receiver's prior knowledge enhances the amount of information conveyed via cheap talk. The point of departure is our explicit focus on the dual role of the sender's message in this context: when the receiver has imperfect private information of her own, the sender's message provides information about the true state as well as about the reliability of the receiver's private information. This feature gives rise to the asymmetric response of the receiver's action, where the receiver reacts less to the truthful message and more to the misrepresented one, which is essential in disciplining the sender to be more truthful.
Keywords: D23; D82; 330; Cheap talk; Informed receiver; Kommunikation; Informationsverhalten; Informationsverbreitung; Asymmetrische Information; Theorie